2015
DOI: 10.1097/md.0000000000001889
|View full text |Cite
|
Sign up to set email alerts
|

Can Serum ST2 Levels Be Used as a Marker of Fibrosis in Chronic Hepatitis B Infection?

Abstract: Interleukin 33 (IL-33) is a cytokine belonging to the IL-1 superfamily. Soluble ST2 (sST2) binds to IL-33 and by functioning as trap receptor inhibits signal sending to Th2 via transmembrane ST2. Because Th2-type cytokines play an important role in fibrosis, the aim of this study is to determine whether sST2 can be used as a marker of fibrosis in chronic hepatitis B (CHB) patients or not.The study included 19 healthy controls, 54 patients with CHB, and 14 patients with cirrhosis because of CHB. The aspartate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
0
19
0
2
Order By: Relevance
“…Associated with severe liver damage, increased serum levels of IL-33 and sST2 have been reported in patients with hepatitis B, acute liver failure, acute-on-chronic liver failure, liver cirrhosis, and hepatocellular carcinoma. (20,21) However, the quantification of serum sST2 and IL-33 in ALD patients has not been reported. We obtained serum samples from 20 healthy individuals (age 33.2±10.6 years, 90% male, and 70% White), 20 heavy drinkers (age 41.5±13.3 years, 65% male, and 80% White), and 11 patients with ALD (age 56.7±10.5 years, 90% male, and 100% White).…”
Section: Resultsmentioning
confidence: 99%
“…Associated with severe liver damage, increased serum levels of IL-33 and sST2 have been reported in patients with hepatitis B, acute liver failure, acute-on-chronic liver failure, liver cirrhosis, and hepatocellular carcinoma. (20,21) However, the quantification of serum sST2 and IL-33 in ALD patients has not been reported. We obtained serum samples from 20 healthy individuals (age 33.2±10.6 years, 90% male, and 70% White), 20 heavy drinkers (age 41.5±13.3 years, 65% male, and 80% White), and 11 patients with ALD (age 56.7±10.5 years, 90% male, and 100% White).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that serum levels of sST2 levels may be a reliable biomarker for evaluating the response to therapy for liver diseases causing fibrosis, including NAFLD[67]. …”
Section: Il-33/st2 Axis In Hfd-induced Steatohepatitismentioning
confidence: 99%
“…In fact, sST2 serum levels differ between hepatitis B virus (HBV) infected patients with mild and severe fibrosis. 16 Similarly, the plasma levels of sST2 were found to be associated with disease severity and mortality in patients with HBV-related acute-on-chronic liver failure. Elevated concentrations of this decoy receptor might indicate adverse prognosis in hepatocellular carcinoma.…”
mentioning
confidence: 99%